Wearing powerful words and objects: healing prosthetics. Issue 7 (9th November 2016) - Healy, Margaret
ABSTRACT: In Civilization and its Discontents (1930), Freud proposed that in striving to overcome the vulnerability of our bodies in the face of nature we create supplementary tools (including writing) in order to remove the limits to human functioning. He famously envisaged a civilisation trajectory in which man, striving to overcome his limitations, would increasingly resemble a 'prosthetic God' [James Strachey (ed), Sigmund Freud: Civilization and its Discontents, trans. Joan Riviere (London: The Hogarth Press, 1963), p. 29]. This essay offers a window of understanding onto pre-modern involvement in the ongoing process of extending the limits of self-hood and making the vulnerable, sick and suffering body comprehensible through the prosthetic use of words, symbols and narrative. Studying the widespread medical use of apotropaic textual amulets, word charms and talismans, this essay asks questions about the imagination, memory and healing, arguing that wearing word prosthetics (attached to the body or inscribed on the skin as tattoos) and performing the rituals they often prescribed (reciting, counting, praying, remembering) constituted a highly affective and valuable form of placebo medicine in earlier periods. Further, it contends that complex textual amulets can be apprehended as narrative prosthesis and thus as precursors to the novel in their ability to extend the limits of self-hood and impose some kind of narrative order on chaotic and painful life experience.